Drying a Standing Teak Tree using a Solar Kiln Drying Method - PHONETIP, Khamtan; BOUPHA, Latsamy; PHANOUVONG, Bounyu; SICHALUENE, Oudone; KHAMMANIVONG, Khanxay; BOUAPHAVONG, Douangta (Walailak Journal of Science and Technology (WJST), 2021)
Understanding the rate of drying of standing trees dried by using a solar kiln drying method could help in predicting the change of moisture content in the tree over a period of drying time. The purpose of this study was to observe the change of moisture content profile in a standing tree during drying. A standing Tectona grandis tree was selected for the experiment with a diameter at breast height of 29 cm in a mixed-species plantation. The tree was girdled with 20 cm width at 20cm above ground. For the experiment, the tree was wrapped in a transparent plastic sheet and a black plastic sheet was installed at the bottom with an angle of 39 °C facing Southwest to maximize solar radiation, with the method being modified from the solar kiln method, which is known as a greenhouse type, with 2 layers of plastic cover. The black and white sheets were placed on the inner side for insulation and for collecting heat from the sun’s radiation, while the outer layer was transparent, which allowed radiation to propagate unhindered in the black sheet. In this study, a sensor for temperature and relative humidity (DHT22) was attached inside the wrapped plastic and the data recorded every 6 min. The results showed that drying a standing teak tree from an initial average moisture content of 105 % to a constant point of 60 % took 80 days under the maximum of the collected temperature of 46 °C inside the wrapped plastic; this finding confirmed that the predicted model of recharge and discharge curve was likely accurate.